Seven invertebrates new for the marine fauna of Madeira Archipelago - Wirtz, Peter (2014)
Ocaña and den Hartog (2002) recorded 18 species of sea anemones from Madeira archipelago. During SCUBA dives along the coasts of Madeira and Porto Santo, the present author encountered a further three sea anemone species and several other marine invertebrates not yet recorded for the marine fauna of Madeira Island. Similar to previous publications (e.g. Wirtz 1998, Wirtz 2007, Ocaña & Wirtz 2009), these findings are reported here.